Sociological ontology of the digital public sphere : the case of Web 2.0/3.0 - Andrade, Pedro José de Oliveira (2013)
Digital public sphere is immersed in the present conjuncture of accelerated transformation and probable rupture, which certainly will affect the way we exercise our citizenship in contemporary times. This social and political tsunami is partly based on the change of paradigm of Web 2.0 or Social Web to Web 3.0 or Semantic Web. To clarify such a process, this paper discusses some of the key issues and theoretical positions on public space, from seminal Habermas’s perspective to new problematics raised by the networked society. The author suggests the construction of a Sociological Ontology of Social and Semantic Web, based on a Semantic-Logical Sociology and Methodology. These procedures are applied through the analysis and hermeneutics of a Wikipedia page entitled ‘Web 2.0’, where sociological experimental tools are used, as Semantic-Logical fields, trees and networks, central and peripheral concepts, and trichotomies.